Synthesis and Antimalarial Activity of 1,4-Disubstituted Piperidine Derivatives - Rokhyatou Seck; Abdoulaye Gassama; Sandrine Cojean; Christian Cavé (Molecules, 2020)
In order to prepare, at low cost, new compounds active against Plasmodium falciparum, and with a less side-effects, we have designed and synthesized a library of 1,4-disubstituted piperidine derivatives from 4-aminopiperidine derivatives 6. The resulting compound library has been evaluated against chloroquine-sensitive (3D7) and chloroquine-resistant (W2) strains of P. falciparum. The most active molecules—compounds 12d (13.64 nM (3D7)), 13b (4.19 nM (3D7) and 13.30 nM (W2)), and 12a (11.6 nM (W2))—were comparable to chloroquine (22.38 nM (3D7) and 134.12 nM (W2)).